Visual literacy in the K-12 social studies classroom - Hensley, Matt; Waters, Stewart; Russell, William B. (Teaching and learning social studies., 2023)
"Visual Literacy in the K-12 Social Studies Classroom is an engaging resource that unites pedagogical theory and practical strategies, empowering teachers to foster critical thinking and cultural awareness among students through the interpretation and creation of visual content. Packed with a variety of visual tools, resources, teacher-tested lesson plans, and more, this book showcases the power of leveraging visual literacy to craft authentic and meaningful social studies learning experiences that resonate with learners of all ages"--